Sociological Analysis of the Discourses of the Health Transformation System in the Tenth and Eleventh Governments - Mehrdad Sharifi; ahmad ali hesabi; Nabi’ollah Ider (توسعه اجتماعی)
The purpose of this study is to examine the discourses of the health transformation system in the tenth and eleventh governments. Therefore, the following questions were examined: 1) what discourses have been dominant in the health system in post-revolutionary governments? What signs were emphasized in the comparative study of the health system and its evolution process in Iran after the revolution? What minutes of discourse has the health system emphasized in the ninth and tenth governments, which has been the emphasis of this government and has created a new approach in the field of health? What is the role of health in the social health process and how is their relationship considered? What has the health system got to do with post-revolutionary political discourses? 6) Since everything is political, what is the relationship between power and its attitude towards the health system? The statistical population of the study was the discourses of the health ministers of the tenth and eleventh governments. The central signifier in the present study has been health discourse and initiatives. The results indicate that the most important signs; The Health Transformation Plan has been constructive interaction and cross-sectoral collaboration, reducing medical costs, modernizing the health care network, and providing information.